Deep Trap Characterization and the Kink Effect in AlGaN/GaN HEMTs. Issue 2 (4th March 2022) - Mukherjee, Jayjit; Malik, Amit; Vinayak, Seema; Rawal, D. S.; Dhaka, Rajendra S.
Abstract : This article presents the study of trapping effects in AlGaN/GaN high electron mobility transistors (HEMTs). Conventional methods like temperature-dependent capacitance-voltage (CV) and pulsed-IV (PIV) have been employed to quantify the traps present in the device layers. Apparent threshold voltage (VTH ) instability as well as lag in the drain current after pulsing are evident. The kink in the drain current has been taken up to observe the trapping signature for devices with two different gate lengths. A modified drain and gate pumping methodology which has been designated as pre-measurement run (PMR) has been presented to get a deeper insight into the kink effect in these devices. Constant maximum field (CMF) PMR shows substantial change in the drain current, whereas negligible change for variable maximum field (VMF) PMR is observed, which confirms the dominant impact of trapping within the heterostructure and field assisted detrapping through Poole-Frenkel emission. Multiple traps have also been identified within the epitaxial layers with the E2 trap ( Ea (activation energy) = 0.69 eV) which can be held responsible for the kink observed in the DC characteristics as observed from pulsed drain lag characteristics.